Utilization of Biogas Slurry from Cow Faces and Palm Oil Empty Fruit Bunches Soaking Water on Indigofera Zollingeriana Productivity - A. Rizky; N. Ginting; A. Sadeli; U. Hasanah; S.E. Sinulingga (Talenta Publisher, 2023)
Biogas slurry, a byproduct of biogas technology, can be used as a source of soil organic matter such as manure. This study aimed to examine the effect of giving biogas slurry gas with the input of cow faeces and empty fruit bunches soaking water on the growth (plant height, number of leaves, number of branches, stem diameter and leaf width) of Indigofera zollingeriana. This study was conducted in the village Tadukan Raga, STM Hilir District, Deli Serdang Regency, using Indigofera Zollingeriana for three months. The design was completely randomized (CRD) with three treatments and six replications. The treatment consisted of P0 = control; P1 = 50% biogas slurry (180ml/polybag of plants) P2 = 100% biogas slurry (360ml/polybag of plants). Parameters observed were plant height, number of leaves, leaf width, branches, and stem diameter. The results showed that the administration of biogas slurry gas at a dose of 100% (360 ml/polybag plant) had a significant effect on the number of leaves, a significant effect on leaf width, had an effect which had a significant on the number of leaves, had an insignificant effect on the number of branches and had a significant effect on stem diameter. The best results were the administration of biogas slurry in the Indigofera Zollingeriana plant the administration of a 100% slurry dose (360 ml/polybag of plants) in all treatments, namely plant height, number of leaves, leaf width, number of branches, stem diameter. Based on this, it can be suggested that biogas slurry fertilizer can be used as liquid organic fertilizer to increase the productivity of Indigofera Zollingeriana plants